A multi-analyte LC–MS/MS method for screening and quantification of 16 synthetic cathinones in hair: Application to postmortem cases. (May 2019) - Freni, Francesca; Bianco, Sara; Vignali, Claudia; Groppi, Angelo; Moretti, Matteo; Osculati, Antonio Marco Maria; Morini, Luca
Graphical abstract: Highlights: A method for the determination of 16 synthetic cathinones in hair. Though a low amount of sample, a high sensitivity was achieved. 2 out of 17 postmortem samples provided positive results for 9 different cathinones. Abstract: A multi-analyte method for detection and quantification of 16 synthetic cathinones (known also as "bath salts") in human hair has been developed and fully validated using liquid chromatography–tandem mass spectrometry system. About 20 mg of hair samples, previously washed and homogenized, were ultrasonicated with 1 mL HCl 0.1 M solution. Samples were then extracted using a solid phase extraction procedure (SPE), taken to dryness and reconstituted in 100 μL mobile phase. Finally, they were directly injected into a liquid chromatographic system, coupled with tandem mass spectrometer detector. The validation criteria parameters were satisfactory according with the international guidelines. A LOQ of 5 pg/mg was obtained for 4-fluoromethcathinone (4-FMC), buphedrone, ethcathinone, methcathinone, mephedrone and naphyrone, while the method proved to be more sensitive for 4-methylethcathinone (4-MEC), methedrone, alpha-pyrrolidinopentiophenone (α-PVP), alpha-pyrrolidinohexiophenone (α-PHP), methylenedioxypyrovalerone (MDPV), butylone, ethylone, 3, 4-dimethylmethcathinone (3, 4—DMMC), pentedrone and pentylone, reaching a LOQ of 1 pg/mg. Potential use of bath salts was investigated in postmortem cases of young subjects previously tested positive at least to one traditional drug of abuse. Two samples out of 17 cases analyzed provided positive results for synthetic cathinones. One sample has been divided in two segments of 2.5 cm length each. Both segments were positive for 8 different cathinone derivatives, namely: 3, 4-DMMC, 4-FMC, 4-MEC, α-PHP, α-PVP, methcathinone, methedrone and pentedrone. The second case provided positive results for ethcathinone.